Current Understanding on the Metabolism of Neutrophils - Jeon, Jae-Han; Hong, Chang-Won; Kim, Eun Young; Lee, Jae Man (Immune network, 2020)
Neutrophils are innate immune cells that constitute the first line of defense against invading pathogens. Due to this characteristic, they are exposed to diverse immunological environments wherein sources for nutrients are often limited. Recent advances in the field of immunometabolism revealed that neutrophils utilize diverse metabolic pathways in response to immunological challenges. In particular, neutrophils adopt specific metabolic pathways for modulating their effector functions in contrast to other immune cells, which undergo metabolic reprogramming to ensure differentiation into distinct cell subtypes. Therefore, neutrophils utilize different metabolic pathways not only to fulfill their energy requirements, but also to support specialized effector functions, such as neutrophil extracellular trap formation, ROS generation, chemotaxis, and degranulation. In this review, we discuss the basic metabolic pathways used by neutrophils and how these metabolic alterations play a critical role in their effector functions.